The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1136/thx.2003.009472
|View full text |Cite
|
Sign up to set email alerts
|

Is endosonography guided fine needle aspiration (EUS-FNA) for sarcoidosis as good as we think?

Abstract: Background: Preliminary data show that endosonography guided fine needle aspiration (EUS-FNA) may be an accurate method for diagnosing sarcoidosis. However, these data were obtained in a small selected group of patients with a very high pretest probability of sarcoidosis. This retrospective study reports on the use of EUS-FNA in an unselected group of patients with mediastinal lymphadenopathy of unknown origin. Methods: The EUS database of a single tertiary referral centre was reviewed for patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 27 publications
3
47
1
2
Order By: Relevance
“…In 64% of patients with the final diagnosis of sarcoidosis, multiple, clustered LNs, with a homogenous iso-echoic echo texture with well-demarcated margins ( fig. 2) were observed, as described in seven patients by MISHRA et al [14]. To the current authors, these EUS features are highly predictive for sarcoidosis as they are different from those of malignant LNs but further studies have to confirm these findings.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…In 64% of patients with the final diagnosis of sarcoidosis, multiple, clustered LNs, with a homogenous iso-echoic echo texture with well-demarcated margins ( fig. 2) were observed, as described in seven patients by MISHRA et al [14]. To the current authors, these EUS features are highly predictive for sarcoidosis as they are different from those of malignant LNs but further studies have to confirm these findings.…”
Section: Resultsmentioning
confidence: 45%
“…This corresponds with the results of a recently published study in patients with enlarged mediastinal LNs of unknown origin where the sensitivity and specificity for EUS-FNA was 89% and 96% [14]. Limitations of the latter study are its retrospective design and the fact that in addition to 28 patients with the final diagnosis of sarcoidosis, the final diagnosis was indefinite in 16 patients.…”
Section: Resultsmentioning
confidence: 73%
“…With a higher diagnostic yield and minimal complications, EUS-FNA has been used in the diagnosis of mediastinal lymphadenopathy in benign disease. Recent trials of EUS-FNA in sarcoidosis showed a diagnostic value of 82% [13], sensitivity of 89-100% and specificity of 94-96% [24,25]. Lymphadenopathies in sarcoidosis are typically hilar, and involvement of right paratracheal and aorto-pulmonary window lymph nodes is common (70-76%) [26].…”
Section: Ebus-tbna In Sarcoidosis Diagnosismentioning
confidence: 99%
“…Recent reports show that, with either curvilinear transoesophageal endoscopic ultrasound (EUS) with fine-needle aspiration (FNA) (EUS-FNA) or endobronchial ultrasound (EBUS) with transbronchial needle aspiration (TBNA) (EBUS-TBNA), together referred to hereafter as E(B)US, noncaseating granulomas can be demonstrated upon sampling of the intrathoracic nodes and that, as such, these techniques can contribute to the diagnosis of sarcoidosis [6][7][8][9][10]. Although these reports indicate feasibility, none of them assessed the value of these techniques in routine daily practice, where bronchoscopy remains the first diagnostic step [1].…”
mentioning
confidence: 99%